Nutrients impacts on the abundance of plankton in Penaeus monodon (Fabricius 1798) shrimp ponds at Dumuria, Bangladesh - Ara, Shifat; Kamrujjaman, Md; Kabir, Kazi Ahmed; Naser, M Niamul (Bangladesh Journal of Zoology, 2018)
a